Making nature whole a history of ecological restoration - Jordan, William R. 1944-; Lubick, George M. 1943-.; SpringerLink (Online service). (Washington, DC Island Press, 2011)
Making Nature Whole is a seminal volume that presents an in-depth history of the field of ecological restoration as it has developed in the United States over the last three decades. The authors draw from both published and unpublished sources, including archival materials and oral histories from early practitioners, to explore the development of the field and its importance to environmental management as well as to the larger environmental movement and our understanding of the world. Considering antecedents as varied as monastic gardens, the Scientific Revolution, and the emerging nature-awareness of nineteenth-century Romantics and Transcendentalists, Jordan and Lubick offer unique insight into the field's philosophical and theoretical underpinnings. They examine specifically the more recent history, including the story of those who first attempted to recreate natural ecosystems early in the 20th century, as well as those who over the past few decades have realized the value of this approach not only as a critical element in conservation but also as a context for negotiating the ever-changing relationship between humans and the natural environment. Making Nature Whole is a landmark contribution, providing context and history regarding a distinctive form of land management and giving readers a fascinating overview of the development of the field. It is essential reading for anyone interested in understanding where ecological restoration came from or where it might be going.
Acknowledgments -- Introduction -- 1. Deep History -- 2. Run-Up -- 3. Preconditions -- 4. Invention -- 5. Neglect -- 6. Realization I: Stepping-Stones -- 7. Realization II: Taking Hold -- 8. Realization III: Finding a Voice -- 9. Realization IV: Getting Real -- 10. Realization V: The Relationship -- 11. Current Thinking -- Notes -- Index.
College of Science Library has electronic copy. Kindly send us a message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Electronic reproduction.
Keywords: Restoration ecology; Electronic books